Spontaneous infections of tick-borne blood parasites in splenectomized indigenous sheep and goats in Ibadan, Nigeria - Majaro, O.M.; Dipeolu, O.O. (1986)
Locally purchased indigenous goats of the Red Sokoto breed and West African Dwarf sheep were splenectomized after they had been certified free from any infection with blood or helminth parasite. Clinical observations were made on the splenectomized animals and blood smears were made on every occasion when there was a rise in their temperature. Parasites were seen in the blood of both animals 6 days after splenectomy and those seen from the stained smears were Babesia motasi, Anaplasma ovis, Theileria ovis and Eperythrozoon. The parasitaemia was higher in the sheep than in the goats but while there was anaemia in the latter, there was none in the former. The significance of the results vis a vis the epidemiology of tick-borne infection of small ruminants in Nigeria is discussed.